2019
DOI: 10.1002/ccd.28099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of calcification on percutaneous coronary intervention: MACE‐Trial 1‐year results

Abstract: Objectives The Multi‐center Prospective Study to Evaluate Outcomes of Moderate to Severely Calcified Coronary Lesions (MACE—Trial) was designed to provide further insight on the impact of calcification on procedural and long‐term percutaneous coronary intervention outcomes. Background Prior studies evaluating the impact of lesion calcification on percutaneous coronary intervention outcomes are limited by: retrospective nature, pooled data from multiple studies, or lack of specificity around calcification with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…In asymptomatic FH patients, Pang et al [16] also found more calcified plaques, especially on the left main artery, and a higher calcium score using coronary computed tomography (CT). PCI are high-risk procedures when done in calcified and bifurcated lesions, and recent studies, including a metaanalysis, have shown that these complex features have a major impact on the recurrence of ischemic events and long-term mortality [30,31]. Moreover, in randomized clinical trials, the lesion complexity score was an independent predictor of short-and medium-term ischemic risk.…”
Section: Discussionmentioning
confidence: 99%
“…In asymptomatic FH patients, Pang et al [16] also found more calcified plaques, especially on the left main artery, and a higher calcium score using coronary computed tomography (CT). PCI are high-risk procedures when done in calcified and bifurcated lesions, and recent studies, including a metaanalysis, have shown that these complex features have a major impact on the recurrence of ischemic events and long-term mortality [30,31]. Moreover, in randomized clinical trials, the lesion complexity score was an independent predictor of short-and medium-term ischemic risk.…”
Section: Discussionmentioning
confidence: 99%
“…В другом крупном проспективном исследовании выраженная кальцификация коронарных артерий статистически значимо снижала показатели успеха процедуры и ассоциировалась с более высокой частотой серьезных неблагоприятных сердечно-сосудистых и церебральных событий через 1 год по сравнению с пациентами с отсутствием или минимальным количеством кальция (24,4 против 4,7 %, р < 0,001). При этом данное различие было обусловлено повышенным риском инфаркта миокарда (1,5 против 13,2 %, р < 0,001) и повторной реваскуляризации целевого поражения (0,0 против 6,6 %, р < 0,001) [16].…”
Section: Discussionunclassified
“…Coronary calcification itself is an independent risk factor for stent thrombosis, ISR, and major adverse cardiovascular events (MACE) 2,3,5,28 . The MACE‐Trial evaluated the impact of lesion calcification on PCI outcomes and showed that severe calcification had significant impact on lesion success (83.3 vs 94.7% for none/mild calcification) as well as higher 1‐year MACE rates (24.4 vs 4.7% none/mild calcification) 29 . In addition, extensive calcium can also damage the polymer coating on drug eluting stents (DES) and impair delivery of drug into the vessel wall, hence contributing to long‐term risk of restenosis and target vessel failure (TVF) 4,30,31 …”
Section: Prognosismentioning
confidence: 99%